Pelatihan Pemanfaatan Canva Sebagai Media Pembelajaran bagi Guru Mata Pelajaran Matematika - Maya Sari Wahyuni; Fajar Arwadi; Ahmad Zaki; Irwan Irwan (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2024)
The learning evaluation training in this activity aims to Train on the Use of Canva as a Learning Media for Mathematics Subject Teachers. The special target of this training is mathematics teachers in Jeneponto Regency, South Sulawesi. The methods used are the tutorial method and Q&A using Canva as a learning medium. This activity began with interviews and observations at related institutions/agencies, then coordination was carried out with the chairman of the mathematics MGMP regarding the schedule and place of implementation. Followed by core activities in the form of Canva as a Learning Media training for teachers in Jeneponto Regency. The results of this activity provide knowledge for teachers in improving their abilities and creativity for the use of technology, namely Canva in learning. Participants felt very helped by this activity.